(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2019)
The 8 th International Brachiopod Congress took place in the prestigious venue of the University of Milano, Italy, in September 2018, after the previous edition held in Nanjing, China, in 2015. 150 participants from universities and research institutes from all over the world attended the meeting, from Argentina, Armenia, Austria, Belgium, Canada, China, Czech Republic, Denmark, France, Germany, Hungary, Iran, Israel, Italy, Japan, New Zealand, Poland, Russia, Slovakia, Spain, Sweden, United Kingdom, and United States of America.